Manajemen Filantropi Kebencanaan Terhadap Masyarakat Terdampak Bencana - S. Kaseng, Ernawati (Jurnal Ekonomi dan Riset Pembangunan, 2024)
Disaster philanthropic management is emerging as a crucial approach in the form of providing assistance and support to disaster-affected communities. So the purpose of the study is to describe the management of disaster philanthropy in building disaster-affected communities. This research article uses a research method, namely a literature study. Data collection techniques through the study of books, literature, notes, and various reports related to research problems through collecting library data, reading and recording and processing research materials. Data analysis is carried out through the stages of recording important and relevant parts related to research problems. Then it is compiled, further analyzed to draw conclusions. This research article shows a description of the results of the analysis that Indonesia as a country prone to natural disasters requires disaster philanthropic management to help disaster-affected communities with a crucial approach, through the involvement of voluntary contributions from individuals, organizations, and institutions to provide assistance in disaster management and social needs. On the other hand, disaster philanthropic management has benefits in order to improve community welfare, reduce disaster risk, provide social assistance, increase community capacity, distribute effective assistance, and recover and reconstruct